Conservation social science: Understanding and integrating human dimensions to improve conservation. (January 2017) - Bennett, Nathan J.; Roth, Robin; Klain, Sarah C.; Chan, Kai; Christie, Patrick; Clark, Douglas A.; Cullman, Georgina; Curran, Deborah; Durbin, Trevor J.; Epstein, Graham; Greenberg, Alison; Nelson, Michael P; et al.
Abstract: It has long been claimed that a better understanding of human or social dimensions of environmental issues will improve conservation. The social sciences are one important means through which researchers and practitioners can attain that better understanding. Yet, a lack of awareness of the scope and uncertainty about the purpose of the conservation social sciences impedes the conservation community's effective engagement with the human dimensions. This paper examines the scope and purpose of eighteen subfields of classic, interdisciplinary and applied conservation social sciences and articulates ten distinct contributions that the social sciences can make to understanding and improving conservation. In brief, the conservation social sciences can be valuable to conservation for descriptive, diagnostic, disruptive, reflexive, generative, innovative, or instrumental reasons. This review and supporting materials provides a succinct yet comprehensive reference for conservation scientists and practitioners. We contend that the social sciences can help facilitate conservation policies, actions and outcomes that are more legitimate, salient, robust and effective. Graphical abstract: Highlights: A better understanding of the human dimensions of environmental issues can improve conservation. Yet there is a lack of awareness of the scope and uncertainty about the purpose of the conservation social sciences. We review 18 fields and identify 10 distinct contributions that the social sciences can make to conservation. This review paper provides a succinct reference for those wishing to engage with the conservation social sciences. Greater engagement with the social sciences will facilitate more legitimate, salient, robust and effective conservation.